Chitinase-3-like protein 1, matrix metalloproteinase-9, and monocyte chemoattractant protein-1 as potential biomarkers and treatment targets of adenomyosis - Alvin Setiawan; Hanom Husni Syam; Wiryawan Permadi; Ruswana Anwar; Tita Husnitawati Madjid; Dian Tjahyadi; Putu Doster Mahayasa (Korean Society of Obstetrics and Gynecology, 2024)
Objective This study aimed to investigate the levels of chitinase-3-like protein-1 (CHI3L1), matrix metalloproteinase-9 (MMP-9), and monocyte chemoattractant protein-1 (MCP-1) in adenomyosis, as compared to normal myometrial tissue. These biomarkers may be useful for determining potential treatment targets. Methods This was a correlative, analytical, and observational study with a cross-sectional design. Participants with a diagnosis of moderate-to-severe adenomyosis, as determined through transvaginal ultrasonography and histological examination, and who underwent laparotomy or laparoscopic surgery for the treatment of adenomyosis, were enrolled in the study. Unlike other studies that recruited healthy women as controls, our study used adenomyotic and healthy nonadenomyotic myometria obtained from the same individual. The levels of CHI3L1, MMP-9, and MCP-1 in the biopsy samples were determined using enzyme-linked immunoassay kits, according to the manufacturer's protocol. Results A highly significant increase in the levels of CHI3L1, MMP-9, and MCP-1 was found in adenomyotic tissues compared to non-adenomyotic tissues (P<0.001). A significant positive correlation was found between CHI3L1 and MMP-9 levels (r=0.463; P=0.008), CHI3L1 and MCP-1 levels (r=0.594; P<0.001), and MCP-1 and MMP-9 levels (r=0.680; P<0.001) in adenomyotic tissues. Conclusion CHI3L1 may play a role in the pathogenesis of adenomyosis via the regulation of the MCP-1 and MMP-9 pathways. Therefore, these molecules may serve as biomarkers and potential therapeutic targets for adenomyosis.